Perkembangan Pendidikan di Weltevreden Awal Abad 20 - Fauzan, Rikza; Maryuni, Yuni; Falasifah, Linda (Prabayaksa: Journal of History Education, 2022)
This study aims to provide a historical description of the development of education in Weltevreden (Nieuw Batavia) in the early 20th century. After the move from Oud Batavia to Weltevreden, it also had an impact on the development of education as a community need at that time in the new urban planning system. The method used in this study is the historical method which includes the stages of heuristics, criticism, interpretation, and historiography. Data collection techniques with literature studies of relevant sources. The historical and archaeological facts found show that there are remains that form the basis of the argument for the development of education in Weltevreden. Starting with the emergence of the Javanese medical school (STOVIA) as a pioneer in education in the health sector. Then continued with the establishment of the law school Rechtshoogeschool (RHS) until the formation of the indigenous elite who were partly members of the Volksraad.